TORTOR PINING ANJEI PADA MASYARAKAT SIMALUNGUN KAJIAN TERHADAP ETIKA DAN ESTETIKA - valent tarihoran (Universitas Negeri Medan, 2017)
Pining Anjeitortor dance tortor is entertainment on Simalungun society. Tortor dance creations that this is taken from folklore Simalungun. This study aims to determine how the shape and Ethics and Aesthetics Tortor Pining Anjei the Community Simalungun. To discuss the purpose of the study above, use the theories related to the topic of this research is the theory of the Presentation Form AM. Hermin K theory of Manner and Costum Ethics and Aesthetics of Dharsono theory.Time used in the research to discuss Tortor Pining Anjei In Simalungun Study on Public Ethics and Aesthetics for 2 months ie June 2016 to July 2016. The research site is in Pamatang Raya, Simalungun, North Sumatra. Analysis of the data in this study using a qualitative descriptive, data collection techniques by observation, library research, interviews, and documentation.The results based on the data collected can be seen that Tortor Pining Anjei as dance entertainment for the community Simelungun pick ethical values ​​and aesthetics that can be seen from the movement, as well as the clothing worn in Tortor Pining Anjei. Ethical values ​​contained therein are tortor movement which moved from the activities and habits of the people Simalungun. And also ethics in Simalungun tor tor-like hands that should not be open too wide, and must not exceed the ears. It is clear that a woman should be polite. Ethics in a dress no where used clothing is Marabit Top. However Marabit Top fashion is clothing worn by women Simalungun society. Aesthetic value can be observed from the movement of the arms, legs and head. Motion carried out can be seen with a good, neat, organized, and flexible. In addition to aesthetics in motion, there is also the aesthetic in the distinctive fashion Simelungun like Ragi Pane and suriSuri makes Tortor Pining Anjei more beautiful views.